BMC family practice integrated GP care for patients with persistent physical symptoms: feasibility cluster randomised trial - Meenal Patel; Kirsty James; Rona Moss-Morris; Mark Ashworth; Mujtaba Husain; Matthew Hotopf; Anthony S. David; Paul McCrone; Sabine Landau; Trudie Chalder; on behalf of the PRINCE Primary trial team (BMC Family Practice, 2020)
Abstract Background Patients continue to suffer from medically unexplained symptoms otherwise referred to as persistent physical symptoms (PPS). General practitioners (GPs) play a key role in the management of PPS and require further training. Patients are often frustrated with the care they receive. This study aims to assess the acceptability of an ‘integrated GP care’ approach which consists of offering self-help materials to patients with PPS and offering their GPs training on how to utilise cognitive behavioural skills within their consultations, as well as assessing the feasibility of conducting a future trial in primary care to evaluate its benefit. Methods A feasibility cluster randomised controlled trial was conducted in primary care, South London, UK. GP practices (clusters) were randomly allocated to ‘integrated GP care plus treatment as usual’ or ‘treatment as usual’. Patients with PPS were recruited from participating GP practices before randomisation. Feasibility parameters, process variables and potential outcome measures were collected at pre-randomisation and at 12- and 24-weeks post-randomisation at cluster and individual participant level. Results Two thousand nine hundred seventy-eight patients were identified from 18 GP practices. Out of the 424 patients who responded with interest in the study, 164 fully met the eligibility criteria. One hundred sixty-one patients provided baseline data before cluster randomisation and therefore were able to participate in the study. Most feasibility parameters indicated that the intervention was acceptable and a future trial feasible. 50 GPs from 8 GP practices (randomised to intervention) attended the offer of training and provided positive feedback. Scores in GP knowledge and confidence increased post-training. Follow-up rate of patients at 24 weeks was 87%. However estimated effect sizes on potential clinical outcomes were small. Conclusions It was feasible to identify and recruit patients with PPS. Retention rates of participants up to 24 weeks were high. A wide range of health services were used. The intervention was relatively low cost and low risk. This complex intervention should be further developed to improve patients’/GPs’ utilisation of audio/visual and training resources before proceeding to a full trial evaluation. Trial registration NCT02444520  (ClinicalTrials.gov).